Development of radiopaque FFF filaments for bone and teeth representation in 3D printed radiological objects (Brazilian Journal of Radiation Sciences, 2022)
The use of 3D printing technologies is growing widely, including the possibility of design phantoms for imaging and dosimetry. For that, high attenuation tissues such as cortical bone, dentin and enamel need to be mimicked to accurately produce 3D printed phantoms, especially for Fused Filament Fabrication (FFF) printing technology.  A Radiopaque FFF filament commercially available had been hard to be found; and this study aims to report, step-by-step, the development of a radiopaque FFF filament. A combination of radiopaque substances (Barium Sulfate - BaSO4 and Calcium Carbonate - CaCO3) was selected using the National Institute of Standards and Technology (NIST) XCOM tool theoretical data and added as filler in an Acrylonitrile Butadiene Styrene (ABS) matrix. The filament was homogenized and gone under first characterizations by analyzing its density, Scanning Electron Microscopy (SEM), Computed Tomography (CT) and micro-CT (µCT) scans. Three filaments were produced with different Hounsfield Units (HU) equivalences: XCT-A (1607HU), XCT-B (1965HU) and XCT-C (2624HU) with respective densities of 1.166(6) g/cm³, 1.211(2) g/cm³ and 1.271(3) g/cm³. With these values, high attenuation tissues, such as bones, dentine and enamel, can now be mimicked with FFF 3D printing technology, at a low cost of production.